Implementation of True IoT Vision: Survey on Enabling Protocols and Hands-On Experience - Pavel Masek; Jiri Hosek; Krystof Zeman; Martin Stusek; Dominik Kovac; Petr Cika; Jan Masek; Sergey Andreev; Franz Kröpfl (International Journal of Distributed Sensor Networks)
Internet of Things (IoT) is expected to become a driver in an emerging era of interconnected world through the advanced connectivity of smart devices, systems, and services. IoT goes beyond a broad range of Machine-to-Machine (M2M) communication technologies and covers a wide variety of networking protocols. There exist solutions like MQTT or SIP collecting data from sensors, CoAP for constrained devices and networks, or XMPP for interconnecting devices and people. Also there is a plethora of standards and frameworks (OSGi, AllJoyn) bringing closer the paradigm of IoT vision . However, the main constraint of most existing platforms is their limited mutual interoperability. To this end, we provide a comprehensive description of protocols suitable to support the IoT vision. Further, we advocate an alternative approach to already known principles and employ the SIP protocol as a container for M2M data. We provide description of data structures and practical implementation principles of the proposed structures (JSON and Protocol Buffers are discussed in detail) transmitted by SIP as a promising enabler for efficient M2M communication in the IoT world. Our reported findings are based on extensive hands-on experience collected after the development of advanced M2M smart home gateway in cooperation with the operator Telekom Austria Group.